Menggali Keutamaan Al-Qur’an: Pondasi Ajaran Yang Menyatukan Umat - Chodijah Aliya; Rifqa Zahara Putri; Aminah Aminah; Muhammad Afrizal; Wismanto Wismanto (Moral : Jurnal kajian Pendidikan Islam, 2024)
The Qur'an as the final revelation revealed by Allah SWT has a very central role in shaping the teachings and lives of Muslims. One of the most important aspects of the teachings of the Qur'an is the unity of the people, which can be a foundation in maintaining harmony and solidarity amidst existing differences. The virtues contained in the Qur'an, such as teachings on justice, tolerance, brotherhood, and compassion, provide clear direction for Muslims to unite and work together for the common good. However, amid the diversity of schools of thought, ethnicities, and thoughts in Muslims, it is important to re-explore the basic principles of the Qur'an that can strengthen relations between fellow Muslims. This study aims to explore the virtues of the Qur'an that can be the foundation of teachings that unite Muslims. This study also seeks to understand how these values ​​are applied in the context of the social and cultural life of Muslims, both in the past and in the contemporary era. The method used in this study is a qualitative method, with a thematic interpretation approach to analyze the verses of the Qur'an related to the unity of the people, as well as a study of the hadith to explore the teachings of the Prophet Muhammad SAW regarding the unity of the Muslim community. In addition, this study also uses a historical and socio-cultural approach to understand the application of the teachings of the Qur'an in Muslim society from time to time. The results of the study show that the virtues of the Qur'an, such as teachings on brotherhood, justice, and tolerance, have a very important role in strengthening the unity of Muslims, even though there are differences in terms of schools of thought, culture, and views. The Qur'an provides clear guidelines that differences are not a reason to divide, but rather a blessing that enriches the diversity of Muslims. By exploring and applying the teachings of the Qur'an, Muslims are expected to be able to better maintain unity and harmony in facing the challenges of the increasingly plural and complex modern era.